Multiple sexual signals: calls over colors for mate attraction in an aposematic, color-diverse poison frog - Dreher, Corinna E.; Pröhl, Heike (Frontiers in Ecology and Evolution, 2014)
Sexual signals indicate species identity and mate quality, and their importance for mate attraction is largely recognized. Recently, research in animal communication has started to integrate multiple signal modalities and evaluate their interactions. However, mate choice experiments across animal taxa have been limited to laboratory conditions, and assessments of multiple sexual signals under field conditions are still lacking. We take advantage of the divergence in visual and acoustic signals among populations of the Neotropical poison frog Oophaga pumilio to evaluate the importance of male advertisement calls and color patterns in female mate selection. Previous mate choice experiments in this species suggested color-assortative female mate preferences across many populations. Nevertheless, acoustic signals are crucial for sexual selection in frogs, and males of O. pumilio use advertisement calls to attract females. We hypothesize that both advertisement calls and coloration affects female mate selection in O.pumilio. To test this hypothesis we tested 452 receptive females from six populations in Costa Rica and Panama in their natural home ranges for preferences regarding local vs. non-local advertisement calls and color patterns. Overall, the calls overrode the effect of coloration, whereby most females preferred local over non-local calls. We found a tendency to prefer brighter (but not necessarily local) males in two populations. Furthermore the strength of preferences varied geographically, and thus might be involved in prezygotic isolation among populations. The stronger effect of calls on mate attraction is associated with acoustic divergence between genetic groups in the species, while colour pattern diversity is mostly located within one genetic group, i.e. not linked to large-scale population structure. Finally our data highlights the importance to consider an array of signal modalities in multiple wild populations in studies of behavioral isolation.